2007
DOI: 10.1111/j.1469-8986.2007.00542.x
|View full text |Cite
|
Sign up to set email alerts
|

Heart‐rate and blood‐pressure variability during psychophysiological tasks involving speech: Influence of respiration

Abstract: Changes in heart-rate and systolic arterial pressure variability (HRV and SAPV) indexes have been used in psychophysiology to assess autonomic activation, including during tasks involving speech. The current article clearly demonstrates in a sample of 25 adult subjects that the erratic and broadband respiratory patterns during such tasks violate the usual assumption that respiration is limited to the high-frequency band (0.15-0.4 Hz). For these tasks, interindividual differences and rest-task changes in HRV an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
60
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 47 publications
2
60
0
1
Order By: Relevance
“…For instance, healthy participants occasionally breathe at frequencies slower than 0.15 Hz (up to 35% of participants; Hoit and Lohmeier, 2000; Beda et al, 2007; Pinna et al, 2007) – this has also been observed in physically fit individuals (Saboul et al, 2014). Breathing below 0.15 Hz dramatically increases the observed power of RSA over that of typical breathing frequencies due to the involvement of the baroreflex.…”
Section: Potential Methodological Controlsmentioning
confidence: 76%
“…For instance, healthy participants occasionally breathe at frequencies slower than 0.15 Hz (up to 35% of participants; Hoit and Lohmeier, 2000; Beda et al, 2007; Pinna et al, 2007) – this has also been observed in physically fit individuals (Saboul et al, 2014). Breathing below 0.15 Hz dramatically increases the observed power of RSA over that of typical breathing frequencies due to the involvement of the baroreflex.…”
Section: Potential Methodological Controlsmentioning
confidence: 76%
“…This is especially important to monitor in populations known to have slower (e.g., athletes32) or faster (e.g., children and adolescents33) respiratory frequencies. Indeed, up to one in five individuals in a sample of healthy participants have been shown to breathe at frequencies slower than 0.15 Hz, which equates to one breath every 6.7 seconds34. Including such participants would violate normal cardiorespiratory assumptions if conventional HF-HRV spectral frequency bands are used.…”
mentioning
confidence: 99%
“…In speech tasks HF HRV is less efficient, a marker of autonomic function than in non-speech tasks. 36 In addition, responses to psychological stress in children are thought mainly to reflect changes in vascular resistance, and chronotropic or inotropic influences in the heart are lower than in adults. 18,37 One limitation in our study is that we had to rely on indirect measures of CV activity.…”
mentioning
confidence: 99%